Weighted Gene Correlation Network Analysis Reveals Key Regulatory Genes Influencing Selenium Enrichment and Yield with Exogenous Selenite in Tartary Buckwheat - Xueling Ye; Linsen Mei; Zhen Gan; Zhiqiang Wang; Wenjun Sun; Yu Fan; Changying Liu; Qi Wu; Yan Wan; Xiaoyong Wu; Dabing Xiang (Plants, 2025)
Selenium (Se) is an essential trace element for human health, and dietary Se intake is an effective supplement. Rich in nutrients and functional components with potential for Se enrichment, Tartary buckwheat (Fagopyrum tataricum (L.) Gaertn.) is a Se-biofortified cereal. To determine the optimal Se treatment concentration and fully understand its effects on Tartary buckwheat, sodium selenite (Na2SeO3) in different concentrations was sprayed onto leaves of Tartary buckwheat at the initial flowering stage. Agronomic and yield-related traits and Se enrichment were analyzed between CK and treatments. The results showed that Na2SeO3 concentrations of 3.0 and 6.0 mg/L significantly increased the contents of Se and starch in the grains, the 1000-grain weight, the number of grains per plant, and the yield. The 6.0 mg/L treatment had the best effect. Transcriptome and weighted gene co-expression network analyses showed that selenite promoted chlorophyll synthesis and photoelectron transport by upregulating chlorophyll synthase (CHLG) and protein CURVATURE THYLAKOID 1B (CURT1B) levels, improving photosynthesis, increasing sucrose synthesis and transport in leaves and starch synthesis and accumulation in grains, and promoting grain-filling and yield. These changes were regulated by genes related to photosynthesis, sucrose, and starch metabolism-related genes, including CAB3C, HPR3, SUS5, BAM9, SS3, SWEET1, and SWEET12. Selenite absorption in Tartary buckwheat was regulated by aquaporin genes NIP1-1 and PIP1-5. Selenite transport was regulated by the inorganic phosphate transporter gene PHT1-1, and organic Se transport was controlled by the proton-dependent oligopeptide transporters NPF3.1 and NPF4.6. Methionine gamma-lyase (MGL) was involved in selenocompound metabolism. This study identified the best spraying scheme for enhancing Se content in the grains. It also revealed the regulatory genes responding to selenite absorption, transport, and metabolism and the regulatory pathways promoting yield in Tartary buckwheat. These results provide technical guidance and theoretical support for producing high-yielding and Se-enriched Tartary buckwheat.